Chronic alcohol consumption exacerbates murine cytomegalovirus infection via impairing nonspecific and specific NK activation in mice. Issue 1 (26th November 2018) - Little, Alex; Li, Yuanfei; Zhang, Faya; Zhang, Hui
Abstract: Chronic alcohol consumption increases the susceptibility to infectious diseases by compromising the immune system. Cytomegalovirus infection is common in humans and usually is asymptomatic in immunocompetent people. However, it can induce life‐threatening medical complications in immunocompromised individuals such as alcoholics. How chronic alcohol consumption exacerbates cytomegalovirus infection is not known. Herein, we used a mouse cytomegalovirus model to study the underlying cellular and molecular mechanism. We found that alcohol consumption increased viral titers in spleen after 4 days of infection, enhanced body weight loss and inhibited splenomegaly during the acute phase of infection. Blood level of IFN‐β, splenic IFN‐γ and granzyme B‐producing NK cells were lower in alcohol‐consuming mice than in water‐drinking mice at 12 hours after viral infection. Moreover, alcohol consumption decreased IL‐15‐producing DC after 36 hours infection, inhibited NK cell, specifically Ly49H + NK cell maturation and proliferation 3‐6 days after viral infection. Surprisingly, alcohol consumption enhanced NK cell and CD8 + T‐cell continuous activation and increased granzyme B‐producing cells. However, alcohol consumption decreased the expression of perforin in spleen and liver. Taken together, chronic alcohol consumption exacerbates cytomegalovirus infection via impairing nonspecific and specific NK cell activation, specifically IFN‐γ and perforin production.